An iron oxide -copper bismuth oxide photoelectrochemical cell for spontaneous water splitting. (20th December 2018) - Du, Chun; Yang, Jie; Yang, Jinhui; Zhao, Yunkun; Chen, Rong; Shan, Bin
Abstract: Highly efficient water splitting reaction on hematite photoelectrode has been encumbered by its low photovoltage and photocurrent in a water splitting cell. In this work, a nanostructured hematite photoanode was prepared via a hydrothermal method, and its water oxidation activity was greatly enhanced by the synergetic application of uniform in-situ cobalt-doping and surface modification with fine cobalt iron oxide nanoparticles electrocatalyst. As a result, its remarkable low onset potential of 0.55 VRHE for water oxidation allows the construction of tandem cell with a novel metal oxide photocathode CuBi2 O4, which has already proven reasonably robust photoactivity for water reduction reaction. The photocurrent and long-term stability of this metal oxides based device in alkaline electrolyte for unassisted overall water splitting reaction were investigated. A solar to hydrogen efficiency of 0.15% was measured accordingly on this spontaneous hydrogen production device, without the involvement of precious metal components. Highlights: An onset potential of 0.55 VRHE was measured on modified hematite photoanode. Co doping and surface modification decrease the charge transfer resistances at interface. Integrated device shows a water splitting efficiency of 0.15% without external bias.